Bovine IgG Prevents Experimental Infection With RSV and Facilitates Human T Cell Responses to RSV - Nederend, Maaike; van Stigt, Arthur H.; Jansen, J. H. Marco; Jacobino, Shamir R.; Brugman, Sylvia; de Haan, Cornelis A. M.; Bont, Louis J.; van Neerven, R. J. Joost; Leusen, Jeanette H. W. (Frontiers in Immunology, 2020)
Abstract (words used 262, max word count 350) Respiratory syncytial virus (RSV) infections represent a major burden of disease in infants and are the second most prevalent cause of death worldwide. Human milk immunoglobulins provide protection against RSV. However, many infants depend on processed bovine milk-based nutrition, which lacks intact immunoglobulins. We investigated the potential of bovine antibodies to neutralize human RSV and facilitate-cell immune activation. We show cow's milk IgG (bIgG) and IVIG have a similar RSV neutralization capacity, even though bIgG has a lower ratio of pre-F: post-F binding ratio compared to human IVIG, with the majority of bIgG binding to pre-F. RSV is better neutralized than human IVIG. Consequently, we enriched RSV specific T cells by culturing human PBMC with a mixture of RSV peptides, and used these T cells to study the effect of bIgG and IVIG on the activation of pre F specific T cells. bIgG facilitated T cell activation in a similar manner as IVIG. Moreover, bIgG is able to mediate T cell activation and internalization of pathogens which are prerequisites for inducing an adaptive viral response. Using in vivo mouse experiments, we showed that bIgG is able to bind the murine activating IgG Fc Receptors (FcɣR), but not the inhibiting FcɣRII. Intranasal administration of the monoclonal antibody palivizumab, but also of bIgG and IVIG prevented RSV infection in mice in vivo. The concentration of bIgG needed to prevent infection was approximately 5-fold higher compared to IVIG. In conclusion, the data presented here indicate that functionally active bIgG facilitates adaptive antiviral T cell responses and prevents RSV infection in vitro and in vivo.